Synthesis and design of PSf/TiO2 composite membranes for reduction of chromium (VI): Stability and reuse of the product and the process. Issue 14 (24th July 2014) - Jyothi, M.S.; Padaki, Mahesh; Geetha Balakrishna, R.; Krishna Pai, Ranjith
Abstract: Abstract : The study demonstrates the 100% repeated recyclability of hybrid membranes without any pretreatment. Composite membranes designed with titanium dioxide (TiO2 ) nanoparticles (NPs) and polysulfone (PSf) membranes were used for reduction of chromium (Cr) (VI) to Cr (III) under sunlight. Different concentrations of TiO2 NPs varying from 1.5% to 2.5% with the difference of 0.5% were incorporated into the membrane matrix. Increase in weight percentage of TiO2 particles enhances the reduction to 100% within 2.5 h with an increase in recyclable capacity as well. The effect of recycling on the surface of the membrane was studied using x-ray diffraction (XRD), scanning electron microscope (SEM), and atomic force microscopy (AFM). The observations in general indicate an increase in roughness without affecting the catalytic efficiency up to six recycles. The study on surface membrane morphology and catalytic efficiency with reusability opens a scope for a feasible economical chromium reduction via a membrane process. Macro and micro structure of the membrane before reduction and after recycling were studied and compared with scientific evidence. Based on the results, the kinetic model was proposed for the reduction reactions.